Neotropical flowering epiphyte diversity: local composition and geographic affinities - Cascante-Marín, Alfredo (2013)
Worldwide, the highest diversity of vascular epiphytic plants resides in the Neotropics. The general pattern of taxonomic composition of the neotropical epiphytic flora has been described, but information regarding the magnitude and geographic distri bution of species richness is lacking. In this paper, we carried out a regional scale analysis in order to provide an overview of the richness, composition and geographic affinities among several neotropical epiphyte floras. Our database comprised 7,524 flowering epi phyte species (48 % of the estimated total of neotropical epiphytes) from eight represen tative localities with politically-defined boundaries. The epiphyte quotient (e.g., percentage of epiphyte species in the total flora) per locality ranged from 5.2–27.7 % (mean: 17.5 %) of the flowering plants. Ecuador represented the most species diverse locality (4,247 spp.), followed by Costa Rica (2,611 spp.). At the family level, the epiphyte composition among localities was roughly homogeneous and dominated by emblematic epiphytic groups: Orchidaceae, Bromeliaceae, and Araceae. However, the generic composition of the epi phytic floras was more heterogeneous. Ecuador and Cuba showed the highest epiphyte endemism (37 and 26 %, respectively), and in some cases vascular epiphytes represented 30 % or more of the total endemic flowering plants at a particular locality. From the available information, four main regional epiphyte floras were identified: the northwestern Andean region, the northern and southern Mesoamerican regions; Cuba as a representative of the Caribbean region remained as a separated group, though weakly related to the Mesoamerican groups. This study identified important geographic localities as targets for the conservation of neotropical epiphyte diversity